A textbook of hydraulic machines for engineering students of various disciplines and competitive examinations (in SI units) - Rajput, R. K. (New Delhi S. Chand, 2016)
Written primarily for the students of Civil and Mechanical engineering, (3z(BA Textbook of Hydraulic Machines(3y (Bhas been written in lucidly and captures the essence in an apt and non-repetitive manner. Aided by a number of solved problems, including typical examples from examination point of view, the book has been a benchmark in the subject for close to 20 years.s
Keywords: Hydraulic machines